Occurrence of fixed Drug Eruptions in a Tertiary Care Hospital: Case Reports - S, Vijayakumar; D, RamChandra; R, Narmadha (Indian Journal of Pharmacy Practice)
Fixed drug eruption (FDE) is a unique pattern of cutaneous drug reaction, characterized by skin lesions that recur at the same site or sites each time the drug is administered. Acute lesions appear as round or oval, sharply marginated, erythmateous plaques that sometimes develop central bullae. They are generally under reported with different rates in different health care systems. The present case studies were carried out in the department of dermatology in a multidisciplinary tertiary care government hospital for one month from June 12th to July 12th, 2011 by the Department of Pharmacy Practice. The cases were recorded and subjected to descriptive analysis. We observed four cases with FDE possibly induced by Isoniazid, Diclofenac, Primaquine, Ciprofloxacin and Carbamazepine. Clinical patterns and drug causing cutaneous ADRs are similar to other researchers. The case studies highlighted that above medications belongs to the group of drugs that can induce fixed drug eruption.
Keywords: Fixed Drug Eruptions; Skin rashes; Pruritus; and Hypersensitivity